2003
DOI: 10.1111/j.1468-2885.2003.tb00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Theory to Design Evaluations of Communication Campaigns: The Case of the National Youth Anti-Drug Media Campaign

Abstract: We present a general theory about how campaigns can have effects and suggest that the evaluation of communication campaigns must be driven by a theory of effects. The National Youth AntiDrug Media Campaign illustrates both the theory of campaign effects and implications that theory has for the evaluation design. Often models of effect assume that individual exposure affects cognitions that continue to affect behavior over a short term. Contrarily, effects may operate through social or institutional paths as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
148
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(156 citation statements)
references
References 20 publications
3
148
0
5
Order By: Relevance
“…The fact that active participation preferences did not predict Internet use one year later does not necessarily mean that Internet use is not influenced by the extent to which cancer patients prefer an active role in medical decision making. Scholars have noted that one of the methodological challenges involved in designing panel surveys is to adopt time lags which can adequately capture both media effects and media selectivity [44, 45]. If a longitudinal survey design does not match the expected time lag between a hypothesized cause and effect, researchers may come to an erroneous conclusion about causal effects.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that active participation preferences did not predict Internet use one year later does not necessarily mean that Internet use is not influenced by the extent to which cancer patients prefer an active role in medical decision making. Scholars have noted that one of the methodological challenges involved in designing panel surveys is to adopt time lags which can adequately capture both media effects and media selectivity [44, 45]. If a longitudinal survey design does not match the expected time lag between a hypothesized cause and effect, researchers may come to an erroneous conclusion about causal effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies (e.g., Hornik et al, 2001; Maxwell, 2002) have reported that some interpersonal communication networks, such as those of sensation-seeking adolescents, often encourage conversations about health-threatening behaviors (e.g. binge drinking, marijuana use).…”
Section: Discussionmentioning
confidence: 99%
“…Health communication campaigns may come before the interpersonal communication concerning the topic addressed by the campaigns. Communication campaigns artificially and strategically increase public information flow about a certain topic, and this increased information may facilitate interpersonal interactions about the campaign itself or the topic of the campaign (Hornik et al, 2001; Southwell & Yzer, 2007). This is particularly true when the topic of the campaign is not something that is often thought about or frequently talked about in our daily lives (e.g., the HPV vaccine).…”
Section: The Relationship Between Media Use and Interpersonal Communimentioning
confidence: 99%
“…2 Many campaigns aim to directly affect individual recipients by invoking cognitive or emotional responses. Such programmes are intended to affect decision-making processes at the individual level.…”
Section: Direct and Indirect Methods To Affect Behaviour Changementioning
confidence: 99%